Patterns and drivers of regeneration of tree species in forests of peninsular Spain - Vayreda, Jordi; Gracia, Marc; Martínez-Vilalta, Jordi; Retana, Javier (Journal of Biogeography, 2013)
Aim Our study aimed to identify and explore the main factors that influence tree recruitment of multiple species at a regional scale across peninsular Spain, an understanding of which is essential for predicting future forest species composition in the face of ongoing environmental change. The study focused on the dynamics of the key transition phase from saplings to adult trees. Location The forests of peninsular Spain. Methods We used the extensive network of plots sampled in two consecutive Spanish national forest inventories (> 30,000 plots) to identify the factors that determine regeneration patterns of the 10 most abundant forest species of Spain at relatively large temporal (c. 10 years) and spatial scales (across Spain): five coniferous species of Pinus (pines) and five broadleaved species of the genera Fagus and Quercus. We fitted separate generalized linear models for the pine species and the broadleaved species to assess the response of sapling abundance and ingrowth rate to the spatial variability of climate (temperature, water availability and recent warming), forest structure (tree density, understorey and overstorey canopy cover, and basal area change) and disturbances (previous forest logging, wildfires and grazing). Results Mean sapling abundance was four times higher for broadleaved species than for pines, while mean annual ingrowth was twice as high. Sapling abundance and ingrowth rate were mainly determined by stand structure, both in pines and broadleaved trees. The direct effects of disturbances and climate were comparatively smaller, and there was no detectable effect of recent warming. Main conclusions The higher values of ingrowth rate of broadleaved species can be explained by their ability to maintain a higher sapling bank due to their greater shade tolerance. This differential response of pines and broadleaved species to canopy closure suggests a probable increase in broadleaved species at the expense of pines. This transition could occur earlier in stands with faster canopy closure dynamics. Spatially explicit, mixed-species demographic models incorporating both the ingrowth and the tree mortality components are needed for predicting the composition of future forests.
Keywords: Broadleaved trees; climate warming; conifers; disturbance; ingrowth rate; national forest inventory; sapling abundance; shade tolerance; Stand Structure; Water availability

Spatial Patterns and Predictors of Forest Carbon Stocks in Western Mediterranean - Vayreda, Jordi; Gracia, Marc; Canadell, Josep G; Retana, Javier (Ecosystems, 2012)
Mediterranean semi-arid forest ecosystems are especially sensitive to external forcing. An understanding of the relationship between forest carbon (C) stock, and environmental conditions and forest structure enable prediction of the impacts of climate change on C stocks and help to deﬁne management strategies that maximize the value of forests for C mitigation. Based on the national forest inventory of Spain (1997–2008 with 70,912 plots), we estimated the forest C stock and spatial variability in Peninsular Spain and, we determined the extent to which the observed patterns of stand C stock can be explained by structural and species richness, climate and disturbances. Spain has an average stand C stock of 45.1 Mg C/ha. Total C stock in living biomass is 621 Tg C (7.8% of the C stock of European forests). The statistical models show that structural richness, which is driven by past land use and life forest history including age, development stage, management activities, and disturbance regime, is the main predictor of stand tree C stock with larger C stocks in structurally richer stands. Richness of broadleaf species has a positive effect on both conifer and broadleaf forests, whereas richness of conifer species shows no signiﬁcant or even a negative effect on C stock. Climate variables have mainly an indirect effect through structural richness but a smaller direct predictive ability when all predictors are considered. To achieve a greater standing C stock, our results suggest promoting high structural richness by managing for uneven-aged stands and favoring broadleaf over conifer species.
Keywords: conifer and broadleaf forests; fire disturbance; Forest management; national forest inventory; Peninsular Spain; structural richness; tree carbon stock; Tree species richness; understory carbon stock; Water availability

Loss of water availability and stream biodiversity under land abandonment and climate change in a Mediterranean catchment (Olzinelles, NE Spain) - Otero, Iago; Boada, Martí; Badia, Anna; Pla, Eduard; Vayreda, Jordi; Sabaté, Santi; Gracia, Carles a.; Penuelas, Josep (Land Use Policy, 2011)
In the north rim of the Mediterranean region, where forest cover is increasing as a result of land abandonment and temperatures are rising as a result of climate change, there is increasing interest for the effects of such changes on the runoff of water courses. This is a paramount issue for the conservation of many freshwater habitats and species. In this work we studied the effects of both an increase in forest cover after depopulation and land abandonment and an increase in temperature on the runoff of a Mediterranean catchment and on the aquatic and semi-aquatic fauna species of the stream (Olzinelles valley, NE Spain). Although in our simulation no decreasing trend in runoff is detected, the monthly runoff-rainfall ratio is now 15% lower than 30 years ago, a fact that may be attributed to a drier period rather than to the small afforestation experienced by the catchment in the last decades. Other factors such as increasing temperatures, changing rainfall patterns and increasing canopy cover are discussed. The observed decrease in the water ﬂow has caused the disappearance of white-clawed crayﬁsh (Austropotamobius pallipes), Mediterranean barbel (Barbus meridionalis), chub (Squalius cephalus), European eel (Anguilla anguilla), and southern water vole (Arvicola sapidus). Our results suggest that in a progressively warmer climate, and especially after land abandonment processes, management of Mediterranean mountain areas should be oriented towards an appropriate distribution of agrarian and forest land-covers in terms of water availability. Down to the stream scale, the pools that keep water throughout the year should be conserved and extended to enhance its potential to maintain aquatic and semi-aquatic species populations
Keywords: Aquatic fauna; Land-cover change; Mediterranean catchment; Warming; Water courses

Large-scale environmental correlates of forest tree distributions in Catalonia (NE Spain) - Thuiller, Wilfried; Vayreda, Jordi; Pino, Joan; Sabaté, Santi; Lavorel, Sandra; Gracia, Carles (Global Ecology and Biogeography, 2003)
Aim To explore the environmental correlates of tree species distributions in Catalonia according to the chorological status of the species. Location The study area is the region of Catalonia, in northeastern Spain. Methods We used presence-absence data for 24 species, sampled in random plots distributed throughout forests of Catalonia. A climate model for the Catalonia region provided environmental variables. We used classiﬁcation tree analysis to explore the environmental correlates of the realized niches of tree species. The predictive accuracy of the models was assessed using the ROC curve approach. Potential distribution maps of tree species were generated for the whole Catalonia region. Results Models were ranked from low to high accuracy for the 24 species. Differences in accuracy among species were related to the chorological status of species. Zonal species, or species at the core of their range (Mediterranean and SubMediterranean species), were generally well predicted, while extrazonal species, or species at the edge of their range, were predicted only moderately well. Mediterranean species distributions showed good correlations with extreme temperatures and annual precipitation. Main conclusions The above trends conﬁrmed the difﬁculty of identifying the realized niche of species at the edges of their ranges. In contrast, Mediterranean and Sub-Mediterranean species, which were at the core of their range, were well-predicted, conﬁrming the importance of extremes of temperature and annual precipitation as effective surrogates for variables having more direct physiological roles in limiting the ability of plants to survive and grow. Maps of potential tree distributions allowed us to deﬁne suitable habitats and to highlight areas where species have been planted outside their natural distribution.
Keywords: chorology; classification tree analysis; environmental gradients; forest trees; potential distribution maps; realized niche; Spain

Large-scale environmental correlates of forest tree distributions in Catalonia (NE Spain) - Thuiller, Wilfried; Vayreda, Jordi; Pino, Joan; Sabaté, Santi; Lavorel, Sandra; Gracia, Carles (Global Ecology and Biogeography, 2003)
Aim To explore the environmental correlates of tree species distributions in Catalonia according to the chorological status of the species. Location The study area is the region of Catalonia, in northeastern Spain. Methods We used presence-absence data for 24 species, sampled in random plots distributed throughout forests of Catalonia. A climate model for the Catalonia region provided environmental variables. We used classiﬁcation tree analysis to explore the environmental correlates of the realized niches of tree species. The predictive accuracy of the models was assessed using the ROC curve approach. Potential distribution maps of tree species were generated for the whole Catalonia region. Results Models were ranked from low to high accuracy for the 24 species. Differences in accuracy among species were related to the chorological status of species. Zonal species, or species at the core of their range (Mediterranean and SubMediterranean species), were generally well predicted, while extrazonal species, or species at the edge of their range, were predicted only moderately well. Mediterranean species distributions showed good correlations with extreme temperatures and annual precipitation. Main conclusions The above trends conﬁrmed the difﬁculty of identifying the realized niche of species at the edges of their ranges. In contrast, Mediterranean and Sub-Mediterranean species, which were at the core of their range, were well-predicted, conﬁrming the importance of extremes of temperature and annual precipitation as effective surrogates for variables having more direct physiological roles in limiting the ability of plants to survive and grow. Maps of potential tree distributions allowed us to deﬁne suitable habitats and to highlight areas where species have been planted outside their natural distribution.
Keywords: chorology; classification tree analysis; environmental gradients; forest trees; potential distribution maps; realized niche; Spain